The current state of Nursing Informatics - an international cross-sectional survey - Laura-Maria Peltonen; Lisiane Pruinelli; Charlene Ronquillo; Raji Nibber; Erika Lozarda Perezmitre; Lorraine Block; Haley Deforest; Adrienne Lewis; Dari Alhuwail; Samira Ali; Martha K Badger; Gabrielle Jacklin Eler; et al. (Sosiaali- ja terveyshuollon tietojenkäsittely-yhdistys, 2022)
An international survey to explore current and future trends in Nursing Informatics (NI) was done in 2015. This article explores responses to questions about: what should be done to further develop NI as an independent discipline; existing policies and standards influencing NI; perceived support towards NI as a discipline; and advice from NI specialists to students and emerging professionals.
Nurse and allied health professionals in academia and practice were reached with snowball sampling. Open-ended questions were analysed with thematic content analysis and the mean and standard deviation is reported for the perceived support towards NI (scale ranging from 1 (not at all supportive) to 10 (very supportive)).
A total of 507 respondents from 46 countries responded to the survey. Respondents reported mediocre support towards NI from the environment (M 5.79, SD 2.60). Results showed that NI education needs development to better meet practice demands, that current NI resources seem insufficient, that NI expertise is not used to its full potential in health institutions and the community, and that NI needs to show its value through research and increase visibility to be recognised among stakeholders worldwide.
In conclusion, there is a need to clarify NI as a discipline and a need for strong leadership to impact policy making. An increase in NI teaching at undergraduate level in nursing as well as an increase in postgraduate NI programmes worldwide would better support practice demands. National policies and international white papers in NI are needed to guide resource distribution to better support practice.